Lithium Intoxication Presenting as a Mixed Misidentification Syndrome - S. G. Potts (Behavioural Neurology)
A case is reported of lithium intoxication presenting with a mixed misidentification syndrome including features of Capgras syndrome. CT scanning showed cerebral atrophy, greater on the right, consistent with earlier evidence, suggesting that misidentification syndromes are more common with right hemisphere lesions.